Tissue culture technique was used to obtain salt tolerant variants from embryogenic calluses of sugarcane (Saccharum sp. var. CP48-103) that cultured on a selective medium containing different levels of NaCl (0, 0.2, 0.4, 0.6, and 0.8% NaCl). A total of four plants regenerated from the tolerant calluses were selected but the best of them in vigor grown in in vitro and hydroponic systems under salinity stress to comparison with source variety. With increasing supply of NaCl in both systems, root - MAHMOUD SHOMEILI; MAJID NABIPOUR; MOSA MESKARBASHEE; HAMID RAJABI MEMARI (HAYATI Journal of Biosciences, 2011)
Tissue culture technique was used to obtain salt tolerant variants from embryogenic calluses of sugarcane (Saccharum sp. var. CP48-103) that cultured on a selective medium containing different levels of NaCl (0, 0.2, 0.4, 0.6, and 0.8% NaCl). A total of four plants regenerated from the tolerant calluses were selected but the best of them in vigor grown in in vitro and hydroponic systems under salinity stress to comparison with source variety. With increasing supply of NaCl in both systems, root growth was more adversely affected than was shoot growth. Chlorophyll contents showed a decreasing trend and dry matter yield of plants reduced but in a slow rate in tolerant somaclonal than source variety. The biochemical analysis showed that at high salt concentration, Cl- and Na+ content in shoot and root increased. With rising salt concentration from 0 to 0.8%, content of Cl- in shoot and root of tolerant variant changed lower than parent showed that this variant had genetic lowest ratio of shoot/root chloride and had minimum transport of Cl- to shoots. Also this variant had high content of Ca2+ in shoot and high K+/Na+ ratio at all salinity levels. Thus it probably has genetic potential to avoid harmful ions uptake.